Variasi Bentuk Bandul Untuk Meningkatkan Pemahaman Peserta Didik Dalam Penentuan Nilai Gravitasi Bumi Pada Ayunan Sederhana - Herma Widya (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2019)
Mathematical pendulum is the most simple tool to use in practice to determine the value of gravity. In the experimental determination of the gravity of the earth which is often done by students usually use spherical shape pendulum. This study will use a variety pendulum of shapes in determination of the value of the earth's gravity. This study aims to improve the understanding of students in materials with a variety simple swing of the pendulum of shapes. The method used in this study is a pre-experimental design with one group pretest posttest, data collection technique is test.